An introduction to law and economics with applications to contract law and governmental regulation - Ulen, Thomas S. (Journal of Public Governance, 2012)
The author starts his essay with a brief overview of law and economics as a research discipline and offers examples of how its analysis differs from that of doctrinal analysis, an older style of legal analysis. Next, he focuses on what he considers to be the two most important developments in the area – the incorporation of behavioural economics into the analysis of law and the emergence of empirical legal studies. After explaining why he considers them to be of such importance, he gives examples of how the legal and regulatory policies suggested by these developments significantly differ from the previous ones.